Influence of dose, gender, and cigarette smoking on clozapine plasma concentrations - Mayerova M (Dove Medical Press, 2018)
Michaela Mayerova,1–3 Libor Ustohal,1–3 Jiri Jarkovsky,4 Jan Pivnicka,1,5 Tomas Kasparek,1,2 Eva Ceskova1,3 1Faculty of Medicine, Masaryk University, Brno, Czech Republic; 2Department of Psychiatry, University Hospital Brno, Brno, Czech Republic; 3CEITEC – Central European Institute of Technology, Masaryk University, Brno, Czech Republic; 4Institute of Biostatistics and Analyses, Masaryk University, Brno, Czech Republic; 5Institute of Forensic Medicine, St. Anne’s University Hospital, Masaryk University, Brno, Czech Republic Introduction: Therapeutic drug monitoring (TDM) of clozapine is a very useful method for verifying both the correct intake and the interindividual variability of its metabolism, thereby avoiding the risk of toxicity. The purposes of this paper were to discover how many patients using clozapine in common clinical practice have clozapine plasma concentration (PC) levels in the proposed reference range and to identify factors that influence clozapine PC levels. Methods: Our study included 100 inpatients (diagnosed with schizophrenia or schizoaffective disorder) taking standard doses of clozapine (100–700 mg/day). Clozapine concentration was measured by high-performance liquid chromatography. Correlations between doses and PC levels and the influence of smoking and gender on clozapine PC levels were calculated. Results: A large number of the patients (67%) had PC levels outside the proposed reference range. The clozapine PC levels were influenced by dose, gender, and cigarette smoking. Conclusion: The correlations between dose, gender, and cigarette smoking and clozapine PC levels highlighted by our study overlap other research. It was surprising to find such a large number of patients with clozapine PC levels outside the therapeutic range. This result suggests the importance of clozapine TDM due to misunderstood inter- and/or intraindividual variability or misestimated partial therapeutic compliance. Keywords: therapeutic drug monitoring, plasma levels, interindividual variability, schizophrenia, schizoaffective disorder